Effects of repeated days of intensified training on muscle glycogen and swimming performance - Costill, D. L.; Flynn, M. G.; Kirwan, J. P.; Houmard, J. A.; Mitchell, J. B.; Thomas, R.; Park, S. H. (Medicine & Science in Sports & Exercise, 1988)
Highly trained swimmers (N = 12) were studied before, during, and after 10 successive days of increased training in an attempt to determine the physical effects of training overload. Training was increased from 4,266 to 8,970 meters per day while intensity was maintained at 94% of VO2max. Subjects experienced local muscular fatigue and difficulty in completing the training sessions. Swimming power, sprinting, endurance performance, aerobic capacity, and muscle (deltoid) citrate synthase, were unchanged at the end of the 10-day period. Four individuals could not maintain the training quality and were forced to swim slower to complete the training distance (they were found to have significantly reduced muscle glycogen levels that resulted from an abnormally low carbohydrate intake). This study suggests that chronic fatigue may be the result of inadequate carbohydrate ingestion as well as overwork. However, for overwork to be detrimental it probably has to last longer than the period used in this investigation. Carbohydrate ingestion appears to be a critical factor involved with training tolerance. It is interesting that complaints of muscle soreness and inability to finish or difficulty in completing training sessions are behavioral symptoms and may be the precursors of physiological breakdown.